Differences between Emotional Intelligence of Active and Inactive Students in Organizations - Ridho, Zaki; Wirdati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This article is based on issues that arise during adolescence, which is the period of transition from youth to adulthood. During this time, adolescents often experience emotional instability, such as defying parents, engaging in negative behaviors, or even contemplating suicide. This is particularly relevant to university students, where those actively involved in organizations face various responsibilities and commitments, while non-active students, who are not involved in organizations, often lack a supportive environment to manage their emotional instability. This issue highlights the low level of emotional intelligence and the challenges faced by university students. It is necessary to address this issue by providing knowledge related to emotional intelligence. This article aims to assess the emotional intelligence of both active and non-active students in organizations, compare the differences between them, and identify the strengths of active versus non-active students in organizations. This study uses a quantitative method with a comparative approach. The population of this research consists of 411 students, with a sample size of 82 students selected through purposive sampling. All respondent data were processed and analyzed using SPSS 23 (Statistical Package for Social Science) software. Based on the results of the research and discussion, the following conclusions can be drawn: There is a difference in emotional intelligence between active and non-active students in organizations, with Ha1 and Ha2 being accepted, as evidenced by a significance value (2-tailed) of 0.018, which is lower than 0.05.